Integrative characterization of tissue-specific 3D genome organization and associated transcriptional regulation in pig liver and muscle - Weiwei Zhou; Yani Huang; Chenyu Li; Mei Ge; Mingfang Zhou; Huashui Ai; Zhiyan Zhang (Functional & Integrative Genomics, 2026)

Antimicrobial-associated adverse events in neonates: an integrated literature review and FAERS pharmacovigilance analysis - Yan Zhang; Jiajia Wang; Baomei Liu; Mingfang Wang; Li Zhuang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

IMEA-Net: An edge-sensitive network for cropland change detection in high-resolution remote sensing images - Xiaoli Yuan; Li Chen; Jiang Zhang; Guoxiong Zhou; Mingfang Wang; Liujun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Oleogel-based frying: quality attributes, food properties and future perspectives – A mini review - Yajing Yang; Mingfang Hua; Xingyue Li; Linhang Qu; Dan Huang; Ke Xie; Qi Li; Siyu Zhang; Yuan Gao; Xiuzhu Yu (Food Chemistry, 2026)

Improving the catalytic performance of glutamate decarboxylase based on sequence co-evolution analysis - Haifeng Pan; Siyi Wang; Yinyi Zhang; Yong Liu; Mingfang Wu; Peilian Wei; Changjiang Lyu; Wenna Bao (Food Bioscience, 2026)

RTCrownNet: A dual-channel deep learning framework for accurate rubber tree crown extraction from UAV LiDAR point clouds - Li Li; Xiangjun Wang; Guoxiong Zhou; Huaiqing Zhang; Yongfei Xue; Mingfang He; Genhua Liu; Hengrui Wang; Hao Li (Computers and Electronics in Agriculture, 2025)

Non-stationary streamflow responses to forest harvesting vary along topographic gradients in a sub-alpine watershed of Southwest China - Shiyu Deng; Mingfang Zhang; Yiping Hou; Zhiwei Jiang; Qiang Li; Shirong Liu (Journal of Hydrology, 2025)

BFlow and Eckhardt methods perform best among non-tracer-based baseflow separation methods - Qiaoqiao Wang; Qiang Li; Yanli Qin; Xuanjiao Chai; Hongli Chen; Yaping Wang; Mingfang Zhang; Dengfeng Liu (Journal of Hydrology, 2025)

Generating reference years of representative cities with typical climate features for the hygrothermal simulation in China - Tingting Zhang; Daniel Zirkelbach; Hartwig M. Künzel; Mingfang Tang; Jing Ren (Energy and Buildings, 2025)

The Role of Iron and Ferroptosis in the Pathogenesis of L-Arginine-Induced Acute Pancreatitis - Peng Zhang; Lulu Fan; Mingfang Teng; Qianhui Wu; Wang Jiaqing; I. P. Korotkova (Bulletin of Experimental Biology and Medicine, 2025)

Bond performance deterioration of rebar in concrete under the temperature synergistic effect: Experimental study - Chunying Zheng; Liangtai Yan; Lizheng Liu; Caiwei Liu; Mingfang Zhang; Wenqing Song (Engineering Structures, 2025)

The in-situ electrochemical impedance spectroscopy unveils the microscopic evolution of vanadium-based cathode materials in aqueous zinc-ion batteries - Jiwei Xie; Zhenggang Jia; Hsu-Sheng Tsai; Mingfang Qian; Xuexi Zhang (Chemical Engineering Journal, 2025)

Homeodomain leucine zipper protein controls the lobed leaf formation by modulating auxin distribution in watermelon - Yimei Zhou; Chuchu Chen; Shiqi Yi; Kejia Zhang; Xiaolong Lyu; Jinghua Yang; Zhongyuan Hu; Mingfang Zhang (Theoretical and Applied Genetics, 2025)

Tree growth response to the 2022 compound drought and heatwave on the eastern Qinghai-Tibetan Plateau - Zhenzhen Wang; Meiying Ji; Jianqiong Luo; Mingfang Zhang; Ning Miao (Forest Ecology and Management, 2025)

The 3PM transformation potential of minimal residual disease in solid tumor management: a bibliometric analysis and review - Yining Chen; Xin Li; Suya Zhao; Yuchong Zhang; Haixu Wang; Fangjian Na; Qi Guan; Zhi Li; Heming Li; Mingfang Zhao (EPMA Journal, 2025)

Efficient photoelectrocatalytic simultaneous removal of antibiotic and Cr(VI) upon novel ternary plasma Ag/AgVO3@3D TiO2: Insight into the synergistic mechanism of redox - Yuqing Gao; Yuzhou Jin; Yu Hu; Mingfang Li; Xuejiang Wang; Haiying Ma; Ya-nan Zhang (Chemosphere, 2025)

Rainfall intensities determine accuracy of canopy interception simulation using the Revised Gash model - Mengliang Ma; Qiang Li; Yaping Wang; Jin Liang; Jiangyao Wang; Jinliang Liu; Mingfang Zhang (Agricultural and Forest Meteorology, 2025)

Local considerations are the key to managing global forests for water - Xiaohua Wei; Julia Jones; Yiping Hou; Shirong Liu; Heidi Asbjornsen; Zhiqiang Zhang; Nadeem Shah; Yanhui Wang; Mingfang Zhang; Irena Creed; Ge Sun; Antonio del Campo; et al. (Science Bulletin, 2025)

Mechanisms of Rehmannioside A Against Systemic Lupus Erythematosus Based on Network Pharmacology, Molecular Docking and Molecular Dynamics Simulation - Guofei Yang; Mingfang Li; Ying Zhang; Xiaohui Li; Tiantian Xin; Jin Hao (Cell Biochemistry and Biophysics, 2024)

Effects of halophyte Suaeda salsa continuous cropping on physical and chemical properties of saline soil under drip irrigation in arid regions - Sihai Liu; Ning Wang; Dongze Li; Changyan Tian; Ke Zhang; Mingfang Hu; Haishan Niu; Zhenyong Zhao (Agriculture, Ecosystems & Environment, 2024)

Forest disturbance thresholds on summer low flows in the interior of British Columbia, Canada - Yiping Hou; Xiaohua Wei; Jinyu Hui; Zhipeng Xu; Ming Qiu; Mingfang Zhang; Qiang Li; Qi Chen (CATENA, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

A review on hygrothermal white-box models of building envelopes in China - Tingting Zhang; Hartwig M. Künzel; Daniel Zirkelbach; Mingfang Tang; Kehua Li; Tobias Schöner; Jing Ren (Energy and Buildings, 2024)

A large presence/absence variation in the promotor of the ClLOG gene determines trichome elongation in watermelon - Yuyuan Ma; Yu Wang; Zhiqin Zhou; Runqin Zhang; Yiru Xie; Yihan Zhang; Yongming Bo; Xiaolong Lyu; Jinghua Yang; Mingfang Zhang; Zhongyuan Hu (Theoretical and Applied Genetics, 2024)

Dual purpose ratooned rice improves agri-food production with reduced environmental cost - Deqiang Qi; Ke Liu; Mingfang Fu; Matthew Tom Harrison; Xiaofei Shi; Xiangchen Liu; Peter de Voil; Yunbo Zhang; Ando Radanielson; Wenge Wu; Jingrui Chen; Yu Jiang; et al. (Journal of Cleaner Production, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Self-powered flexible battery pressure sensor based on gelatin - Peixue Jia; Qixiang Zhang; Ziqi Ren; Jianyu Yin; Dandan Lei; Wenzhong Lu; Qianqian Yao; Mingfang Deng; Yihua Gao; Nishuang Liu (Chemical Engineering Journal, 2024)

A comparison of annual streamflow sensitivities to vegetation change and climate variability in fourteen large watersheds along climate zones in China - Yiping Hou; Mingfang Zhang; Xiaohua Wei; Shirong Liu; Qiang Li; Wenfei Liu; Tijiu Cai; Enxu Yu (CATENA, 2024)

Steric heights of submesoscale processes and internal gravity waves in the subtropical northwestern Pacific and northern South China Sea as revealed by moored observations - Mingfang Miao; Zhiwei Zhang; Jinchao Zhang; Yue Wang; Wei Zhao; Jiwei Tian (Progress in Oceanography, 2023)

A precise apple leaf diseases detection using BCTNet under unconstrained environments - Yukai Zhang; Guoxiong Zhou; Aibin Chen; Mingfang He; Johnny Li; Yahui Hu (Computers and Electronics in Agriculture, 2023)

Allelic variations of ClACO gene improve nitrogen uptake via ethylene-mediated root architecture in watermelon - Kejia Zhang; Wei Gao; Yimei Zhou; Haoshun Zhao; Yuelin Xia; Mengyi Zhang; Yongming Bo; Xiaolong Lyu; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Theoretical and Applied Genetics, 2023)

Structural variation of GL1 gene determines the trichome formation in Brassica juncea - Yiqing Meng; Xiagolong Lyu; Jiaqi Liu; Wei Gao; Yuyuan Ma; Nanqiao Liao; Zhangping Li; Yongming Bo; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Theoretical and Applied Genetics, 2023)

A global synthesis of hydrological sensitivities to deforestation and forestation - Yiping Hou; Xiaohua Wei; Mingfang Zhang; Irena F. Creed; Steven G. McNulty; Silvio F.B. Ferraz (Forest Ecology and Management, 2023)

A systematic review and meta-analysis indicates a substantial burden of human noroviruses in shellfish worldwide, with GII.4 and GII.2 being the predominant genotypes - Yijing Li; Liang Xue; Junshan Gao; Weicheng Cai; Zilei Zhang; Luobing Meng; Shuidi Miao; Xiaojing Hong; Mingfang Xu; Qingping Wu; Jumei Zhang (Food Microbiology, 2023)

Differences in the effectiveness of the high-efficient concentrated pretreatment method on the norovirus detection in oysters and mussels - Yijing Li; Liang Xue; Junshan Gao; Weicheng Cai; Yanhui Liang; Zilei Zhang; Linping Wang; Xiaojing Hong; Luobing Meng; Mingfang Xu; Qingping Wu; Jumei Zhang (International Journal of Food Microbiology, 2023)

An allelic variant in the ACS7 gene promotes primary root growth in watermelon - Ahmed Mahmoud; Rui Qi; Haoshun Zhao; Haiyang Yang; Nanqiao Liao; Abid Ali; Guy Kateta Malangisha; Yuyuan Ma; Kejia Zhang; Yimei Zhou; Yuelin Xia; Xiaolong Lyu; et al. (Theoretical and Applied Genetics, 2022)

Application of galactinol to tomato enhances tolerance to cold and heat stresses - Yudong Liu; Li Zhang; Jian Ma; Sida Meng; Chunpeng Pang; Xiaomeng Zhao; Huidong Zhang; Shou Wang; Tao Xu; Yi He; Yufeng Liu; Mingfang Qi (Horticulture, Environment, and Biotechnology, 2022)

Influence of climates and materials on the moisture buffering in office buildings: a comprehensive numerical study in China - Jinzhong Fang; Huibo Zhang; Peng Ren; Bao-Jie He; Mingfang Tang; Chi Feng (Environmental Science and Pollution Research, 2022)

Transcriptome profiling reveals key genes in regulation of the tepal trichome development in Lilium pumilum D.C. - Yin Xin; Wenqiang Pan; Xi Chen; Yixin Liu; Mingfang Zhang; Xuqing Chen; Fengping Yang; Jingru Li; Jian Wu; Yunpeng Du; Xiuhai Zhang (Plant Cell Reports, 2021)

Nitric oxide alleviates lead toxicity by inhibiting lead translocation and regulating root growth in watermelon seedlings - Jehanzeb Khan; Guy Kateta Malangisha; Abid Ali; Ahmed Mahmoud; Jinghua Yang; Mingfang Zhang; Zhongyuan Hu (Horticulture, Environment, and Biotechnology, 2021)

Evaluating the genetic relationship of Lilium species/cultivars based on target region amplification polymorphism (TRAP) - Yue Hu; Jianwu Ren; Yixin Liu; Mingfang Zhang; The Su Moe; Mohammad Sayyar Khan; Yunpeng Du; Xiuhai Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization of watermelon anther and its programmed cell death-associated events during dehiscence under cold stress - Xiaolong Lyu; Shuna Chen; Nanqiao Liao; Jie Liu; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Plant Cell Reports, 2019)

The seedling and cutting propagation techniques of Acer fabri Hance - Bihua Chen; Bin Jiang; Yongsheng Deng; Juan Zhang; Mingfang Hu; Huihua Fan; Xin Li (Vegetos, 2019)

Vegetation cover—another dominant factor in determining global water resources in forested regions - Xiaohua Wei; Qiang Li; Mingfang Zhang; Krysta Giles‐Hansen; Wenfei Liu; Houbao Fan; Yi Wang; Guoyi Zhou; Shilong Piao; Shirong Liu (Global Change Biology, 2018)
Forested catchments provide critically important water resources. Due to dramatic global forest change over the past decades, the importance of including forest or vegetation change in the assessment of water resources under climate change has been highly recognized by Intergovernmental Panel on Climate Change (IPCC); however, this importance has not yet been examined quantitatively across the globe. Here, we used four remote sensing‐based indices to represent changes in vegetation cover in forest‐dominated regions, and then applied them to widely used models: the Fuh model and the Choudhury‐Yang model to assess relative contributions of vegetation and climate change to annual runoff variations from 2000 to 2011 in forested landscape (forest coverage >30%) across the globe. Our simulations show that the global average variation in annual runoff due to change in vegetation cover is 30.7% ± 22.5% with the rest attributed to climate change. Large annual runoff variation in response to vegetation change is found in tropical and boreal forests due to greater forest losses. Our simulations also demonstrate both offsetting and additive effects of vegetation cover and climate in determining water resource change. We conclude that vegetation cover change must be included in any global models for assessing global water resource change under climate change in forest‐dominant areas.

Over-expression of LlHsfA2b, a lily heat shock transcription factor lacking trans-activation activity in yeast, can enhance tolerance to heat and oxidative stress in transgenic Arabidopsis seedlings - Haibo Xin; Hua Zhang; Xionghui Zhong; Qinglong Lian; Aixiang Dong; Li Cao; Mingfang Yi; Richen Cong (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

The complete chloroplast genome of Lilium taliense, an endangered species endemic to China - Qian Zhang; Yu Bi; Mingfang Zhang; Xuqing Chen; Fengping Yang; Jing Xue; Yunpeng Du; Xiuhai Zhang (Conservation Genetics Resources, 2017)

Genome-wide identification and comparative analysis of grafting-responsive mRNA in watermelon grafted onto bottle gourd and squash rootstocks by high-throughput sequencing - Na Liu; Jinghua Yang; Xinxing Fu; Li Zhang; Kai Tang; Kateta Malangisha Guy; Zhongyuan Hu; Shaogui Guo; Yong Xu; Mingfang Zhang (Molecular Genetics and Genomics, 2016)

Rule-Based Method for Morphological Classification of ST Segment in ECG Signals - Mingfang Xu; Shoushui Wei; Xiuwen Qin; Yatao Zhang; Chengyu Liu (Journal of Medical and Biological Engineering, 2015)

Deficient PKR in RAX/PKR Association Ameliorates Ethanol-Induced Neurotoxicity in the Developing Cerebellum - Hui Li; Jian Chen; Yuanlin Qi; Lu Dai; Mingfang Zhang; Jacqueline A. Frank; Jonathan W. Handshoe; Jiajun Cui; Wenhua Xu; Gang Chen (The Cerebellum, 2015)

Soil salinization research in China: Advances and prospects - Jianguo Li; Lijie Pu; Mingfang Han; Ming Zhu; Runsen Zhang; Yangzhou Xiang (Journal of Geographical Sciences, 2014)

Depression Status and Associated Factors in Chinese Occupational Truck Drivers - Shiqin Shen; Yong Li; Mingfang Zhou; Chan Zhang; Yajin Jiang; Yuanyi Kang (Cell Biochemistry and Biophysics, 2013)

Induction of Neuronal Mitophagy in Acute Spinal Cord Injury in Rats - Datang Yu; Mingfang Li; Bing Ni; Jiming Kong; Zhengfeng Zhang (Neurotoxicity Research, 2013)

Role of a Newly Cloned Alternative Oxidase Gene (BjAOX1a) in Turnip Mosaic Virus (TuMV) Resistance in Mustard - Lei Zhu; Yanman Li; Neelam Ara; Jinghua Yang; Mingfang Zhang (Plant Molecular Biology Reporter, 2012)

Chloroplast-located BjFer1 together with anti-oxidative genes alleviate hydrogen peroxide and hydroxyl radical injury in cytoplasmic male-sterile Brassica juncea - Jinghua Yang; Shan Liu; Xiaodong Yang; Mingfang Zhang (Molecular Biology Reports, 2012)

Identification of Down-regulated Genes Modulated by an Alternative Oxidase Pathway Under Cold Stress Conditions in Watermelon Plants - Yanman Li; Lei Zhu; Baochen Xu; Jinghua Yang; Mingfang Zhang (Plant Molecular Biology Reporter, 2012)

A prospective clinical study in hepatitis B e antigen-negative chronic hepatitis B patients with stringent cessation criteria for adefovir - Minghao Ha; Guotong Zhang; Shu Diao; Mingfang Lin; Liping Sun; Huiyuan She; Chenbao Kuan; Lihui Shen; Chunhong Huang; Wenjuan Shen; Zhongming Huang (Archives of Virology, 2012)

Cloning and characterization of HsfA2 from Lily (Lilium longiflorum) - Haibo Xin; Hua Zhang; Li Chen; Xiaoxin Li; Qinglong Lian; Xue Yuan; Xiaoyan Hu; Li Cao; Xiuli He; Mingfang Yi (Plant Cell Reports, 2010)